Optimization of Microwave Assisted Process for Extraction of Celery Seed Essential Oil - Talwari, Gopika; Ghuman, B. S. (Journal of Agricultural Engineering, 2014)
Microwave assisted extraction (MAE) method was developed for extraction of essential oil from celery seeds. A domestic microwave oven was modified and Clevenger apparatus attached to it to make it an extraction unit. Effect of various parameters such as soaking time, temperature and power density during MAE was studied. A multivariate study based on a Box-Behnken design was used to evaluate the influence of three major variables (soaking time, temperature and power density) affecting the performance of MAE on celery seed. Oil yield, time of extraction and energy consumption (MJ.kg-1 oil) by MAE were determined and compared with those obtained by the traditional hydro-distillation (HD). It was found that microwave assisted process gave approximately same oil yield (1.90%) in less time ( 93.5 min) and with low energy consumption (58191.78 MJ.kg-1 oil). Results revealed that the selected parameters had significant effect on the responses.